The Ability of implementing Cloud Computing in Higher Education - KRG - Ahmed, Zanyar Ali; Jaafar, Ako Abubakar; Ghareb, Mazen Ismaeel (Kurdistan Journal of Applied Research, 2017)
Cloud computing is a new technology. CC is an online service can store and retrieve information, without the requirement for physical access to the files on hard drives. The information is available on a system, server where it can be accessed by clients when it’s needed. Lack of the ICT infrastructure of universities of the Kurdistan Regional Government (KRG) can use this new technology, because of economical advantages, enhanced data managements, better maintenance, high performance, improve availability and accessibility therefore achieving an easy maintenance of organizational institutes. The aim of this research is to find the ability and possibility to implement the cloud computing in higher education of the KRG. This research will help the universities to start establishing a cloud computing in their services. A survey has been conducted to evaluate the CC services that have been applied to KRG universities have by using cloud computing services. The results showed that the most of KRG universities are using SaaS. MHE-KRG universities and institutions are confronting many challenges and concerns in term of security, user privacy, lack of integration with current systems, and data and documents ownership.